Accidental Closantel Poisoning in Sheep in the State of Rio Grande do Sul - Brazil - Blanco Pohl, Camila; Lorenzett, Marina Paula; Santana de Cecco, Bianca; Henker, Luan Cleber; Panziera, Welden; Driemeier, David (Acta Scientiae Veterinariae, 2020)
Background: Verminosis is one of the major health problems in sheep flocks, and is one of the main causes of death in sheep worldwide. Closantel is an antiparasitic drug commonly used in sheep; however, its safety margin is narrow, and this drug may induce intoxication in animals submitted to high doses. Lesions occur mainly in the eyes, and are characterized by edema and compression of the optic nerve, retinopathy, and severe degeneration of ganglia cells. Clinical signs are pupil dilation, which often lead to permanent blindness. This work aims to report an outbreak of sheep mortality due to closantel intoxication, associated with inadequate anthelmintic administration practices. Case: An on-site visit was conducted to a sheep farm, located in the municipality of Osório, Rio Grande do Sul (RS), in which high mortality was reported. The flock consisted of approximately 300 Texel sheep, managed in an extensive grazing system. Lambs and adult animals were affected. According to the information provided by the farm owner, many animals presented clinical signs of haemonchosis, and a closantel dose of 20 mg / lamb was administered in all sheep, regardless of body weight. Lambs weighted on average 13 kg. After closantel administration, several sheep presented neurologic signs and died. At the clinical examination, sheep presented pallor of ocular mucous membranes, as well as submandibular edema. Also, 20 lambs showed signs of blindness, disorientation and bumping into objects, as well as hypothermia and lack of response to the menace reflex. Three 30 to 45-day-old male lambs that died spontaneously were submitted for necropsy. Grossly, only mild ascites was noted. Histopathological examination of the retina showed degeneration and fragmentation of photoreceptor layer as well as depletion of the inner nuclear layer, associated with pyknosis and karyorrhexis. There was also a reduction in the number of ganglia cells in the ganglion cell layer and atrophy and vacuolization in the outer plexiform layer. In the optic nerve, multifocal mild to moderate vacuolization was observed. Diffuse perineural and perivascular edema were observed in the brain, predominantly in the grey matter. In the encephalon of one of the lambs, multifocal vacuolization was observed, which was also evidenced at the junction of the white and gray matter of the telencephalon, and in the white matter of the cerebellum. In the trigeminal ganglia, moderate multifocal vacuolization was noted in the perikaryon of neurons. Furthermore, the spinal cord had moderate multifocal vacuolization at the junction of white and gray matter. Discussion: The diagnosis of closantel intoxication in sheep was based on the clinical history and histopathological findings. The association of these data is crucial to suspect and confirm the diagnosis of this type of intoxication. Closantel is an anthelmintic drug widely used in sheep, and in correct doses may be very effective, but when used in doses higher than recommended may lead to irreversible lesions. The optical damage is derived from edema which leads to degeneration of ganglia cells and injury to the optic nerve. Another proposed mechanism is related to optic nerve compression causing rupture and edema of retinal structures. Lesions tend to be dose related, and poisoning usually occurs when treating groups of animals based on the weight of the heaviest animal. Clinical signs of blindness and pupil dilatation are usually seen. There is no effective treatment for reversion of this condition; therefore, prevention based on correct calculation of anthelmintic dose is pivotal. The epidemiological examination, clinical signs and anatomopathological examination were extremely important to make the final diagnosis of this intoxication.